Discover how fintech is transforming bank performance: insights from an emerging economy - Gokhan Ovenc; Abdul Baghi Nabiyev (Cogent Economics & Finance)
Fintech startups are using new technologies to force traditional banks to change their business models, which could potentially threaten their position in the financial industry. Banks collaborate with fintech startups to enhance their technological infrastructure and gain a competitive advantage. This paper investigates the impact of collaborations between banks and fintech companies on commercial banks’ performance using a panel dataset from 2013 to 2021 in Türkiye. The One-Step System GMM model results vary by the size of banks and bank performance indicators. First, findings indicate that the collaborations between commercial banks and fintech companies have a positive impact only on banks’ ROE for large-scale traditional banks, which indicates a potential complementary effect. Another significant outcome implies that fintech development has a negative influence on banks’ ROA and ROE for large-scale banks, which reveals that specific fintech services and goods can be substituted for traditional banks.